Halloysite clay nanotubes based phase change material composites with excellent thermal stability for energy saving and storage. Issue 24 (17th February 2016) - Liang, Weidong; Wu, Ye; Sun, Hanxue; Zhu, Zhaoqi; Chen, Pinsong; Yang, Baoping; Li, An
Abstract : Superhydrophobic halloysite clay nanotubes based PCM composites with excellent thermal stability have been fabricated. Taking advantage of the simple process and low cost, the composites may have great potential as solar energy storage systems. Abstract : Superhydrophobic PDMS–HNTs (halloysite clay nanotubes) were prepared by the surface modification of purified HNTs (p-HNTs) with polydimethylsiloxane (PDMS). The strong hydrophobic properties and distinctive structure of PDMS–HNTs, resulting from the hollow and tubular structure of p-HNTs, have led to their use as supporting materials in the preparation of form-stable phase change material (PCM) composites, into which PCMs can be easily adsorbed and remain stable without leakage even at temperatures greater than the melting points of the PCMs. The PCMs were loaded at the outer and inner surfaces of PDMS–HNTs, and as a result of their incorporation, the latent heats of the PDMS–HNTs/PCMs composites were measured to be in the range of 44.7–72.1 kJ kg −1 . Taking advantage of the simple process, low cost and excellent thermal stability, the PDMS–HNTs/PCM composites may have great potential for practical applications as solar energy storage systems.